1987
DOI: 10.1021/bi00389a026
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of coenzyme-induced conformational work and binding potential in yeast alcohol and porcine heart lactate dehydrogenases: a hydrogen-deuterium exchange study

Abstract: Binding of NAD coenzymes to yeast alcohol dehydrogenase (YADH) and porcine heart lactate dehydrogenase (PHLDH) was studied by hydrogen-deuterium exchange with the infrared technique. Conformational changes in the enzymes specific to the coenzymes and their fragments were observed, and the pH dependence of the exchange reaction shows that it conforms to the EX-2 scheme. In both YADH and PHLDH the magnitude of the conformational change of measured by exchange retardation is considerably larger for NAD+ than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…85 Hydrogen–deuterium exchange studies also suggest that binding of NAD + results in a conformational change. 86 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Hydrogen–deuterium exchange studies also suggest that binding of NAD + results in a conformational change. 86 …”
Section: Resultsmentioning
confidence: 99%
“…85 Hydrogen−deuterium exchange studies also suggest that binding of NAD + results in a conformational change. 86 The next step in the mechanism, the binding of alcohol to the enzyme−NAD + complex, may occur by direct displacement of Glu-67 by the alcohol or by a double displacement of a water that could bind to the zinc in the enzyme−NAD + complex. The homologous E. coli enzyme complexed with NAD has water bound to the catalytic zinc.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This observation might explain the unsuccessful interaction between full-length CtBP2 and acinus-S in vitro (Fig 1A), which could be rescued in the presence of NAD + (Fig 2A). Since conformational change upon NAD + binding is a key feature of NAD + -dependent dehydrogenase (De Weck et al , 1987), binding of NAD + to CtBP2 would somehow stabilize the C-terminal structure of CtBP2, which favors its binding to acinus-S.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the immobilization of aromatic residues (measured by near-UV CD) in the presence of FBP with that in the absence of FBP also points to a more flexible structure without FBP above 60 °C (data not shown). Numerous studies have shown that the accessibility of peptide hydrogens to solvent is influenced by ligand binding, suggesting that the ligands impose constraints on the dynamics of protein structures (De Week et al, 1987, and references cited therein). It is therefore not astonishing that the point of thermal denaturation of BSLDH is increased by 3 to 5 °C in the presence of FBP (data not shown).…”
Section: Discussionmentioning
confidence: 99%